PENGARUH PENDAPATAN USAHA, BIAYA OPERASIONAL DAN PERPUTARAN TOTAL AKTIVA TERHADAP LABA BERSIH PADA PT MEGA CENTRAL AUTONIAGA MEDAN PERIODE 2013-2017 - ENDANG KURNIATI (LP2MTBM MAKARIOZ, 2019)
Every company basically has a variety of different objectives. The goal is to increase profits, increase employee productivity, improve employee satisfaction and coaching, and the most important is how the company generates profits as large as. Financial performance assessment can be used to find out how much the company profits by comparing. The purpose of this study is to find out and analyze the